ANALISIS PENENTUAN RAFAKSI DAN PENGARUHNYA TERHADAP PILIHAN SALURAN PEMASARAN PETANI UBI KAYU DI KABUPATEN LAMPUNG TENGAH - Kusmaria Kusmaria; Ratna Winandi Asmarantaka; Harianto Harianto (Forum Agribisnis, 2016)
Cassava becomes an important commodity in Indonesia because Indonesia is one of the major producer of cassava in the world. Besides exporting cassava, in fact Indonesia also imported cassava in large quantities. Altough the price of cassava was increasing in Lampung but the production and harvested area were decreasing, moreover factory and trader also set rafaksi on cassavas sold by farmers. Rafaksi is a penalties quantity to assess the quality of cassava farmers. Cassava marketing channels play role in determining the price and rafaksi that received by farmers. The aims of this research are (1) to analyze mechanism of determining rafaksi (2) to analyze price received by farmers’ after obtained rafaksi (3) analyze influence rafaksi to choice of marketing channels cassava farmers in Central Lampung Regency. Primary data were collected rendomly from 74 respondents. Data were analyzed by describe, correlation and binary logistic regression. The results showed that in the perception of farmers, determination of cassava rafaksi determined by several criteria such as the age of harvest, varieties, aci levels and the amount of dirt but not obtained a measure to ensure that criteria and only use the visual observation. The results of correlation analysis showed that there was no statistically significant connection between harvest time and the varieties of cassava with rafaksi of cassava which received by farmers. The result of binary logistic regression analysis showed that rafaksi loan significantly affected the choice of marketing channels.